Cognitive Conflict-Based Conceptual Change Model on Concept Mastery & Student Self-regulation - Haka, Nukhbatul Bidayati; Rohmah, Reni Nur; Hamid, Abdul; Masya, Hardiyansyah (Jurnal Pendidikan MIPA, 2022)
This study aims to determine the effect of the conceptual change model with a cognitive conflict approach on concept mastery & self-regulation of class X students in biology subjects. The quasi-experimental method with posttest only controls group design. The research population is students of class X Mathematics & Natural Sciences, class X Mathematics & Natural Sciences 1 as the experimental class, & X Mathematics & Natural Sciences 2 as the control class. Data collection techniques with concept mastery tests & self-regulation questionnaires. Data analysis used an independent sample t-test. Based on the results of the study, the average value of mastery of concepts in the experimental class was 71.14, & the control class was 65.52. The average selfregulation in the experimental class was 73.29, in the control class it was 65.91. Independent sample t-test test shows that p-value> 0.05. This means that there is an influence of the conceptual change model with a cognitive conflict approach on concept mastery & self-regulation in class X in biology subjects.Keywords: conceptual change, conflict cognitive approach, mastery of concepts, self-regulation DOI: http://dx.doi.org/10.23960/jpmipa/v23i1.pp100-110